2020
DOI: 10.3390/s20113262
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Flow Field on Chemical Detection Performance of Quadrotor Drone

Abstract: The determination of a suitable sensor location on quadrotor drones is a very important issue for chemical reconnaissance platforms because the magnitude and direction of air velocity is different for each location. In this study, we investigated a customized chemical reconnaissance system consisting of a quadrotor drone and a chip-sized chemical sensor for detecting dimethyl-methylphosphonate (DMMP; a Sarin simulant) and investigated the chemical detection properties with respect to the sensor position throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 56 publications
(62 reference statements)
1
18
0
Order By: Relevance
“…Moreover, for PID A sensor the response is linearly proportional to the amount of pollutant in this range of concentration as per Lambert-Beer equation, while the number of counts registered by MOX A, as per its intrinsic characteristic (Figs. 15,16), tends to a plateau with the increasing of contamination.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, for PID A sensor the response is linearly proportional to the amount of pollutant in this range of concentration as per Lambert-Beer equation, while the number of counts registered by MOX A, as per its intrinsic characteristic (Figs. 15,16), tends to a plateau with the increasing of contamination.…”
Section: Discussionmentioning
confidence: 95%
“…Regarding the most suitable positioning of the sensors on the UAV, computational fluiddynamic simulations [16] are available to evaluate the influence that rotor turbulence had on the detection and identification capability and the best compromise between different configurations. A specific study on the best sensor location for the detection of particulate matter in case of a radioactive release had been already published [17].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal location of the sensors requires a study of the airflows produced by the rotors and the analysis of the quad-rotor aerodynamics [17,41] and the hexa-rotor aerodynamics [40]. Such studies, performed using simulations [17,[42][43][44][45][46] and experiments in the real environment [17,40,41,[45][46][47][48][49], showed that the calmest place, with the weakest airflow, is the middle part of the UAV. This applies to both small, several-hundred-gram UAVs [17], to medium-sized ones [41,42,45,47,48] and large, several-kilogram ones [40] as well.…”
Section: Location and Calibration Of The Gas Sensormentioning
confidence: 99%
“…Different approaches have been compared for gas release localization with mobile platforms, and gas sensing systems have been developed and tested specifically for Volatile Organic Chemicals (VOC) [2] and Chemical Warfare Agents (CWAs) [3] localization and mapping. Numerous other applications have demonstrated the drones' suitability to be equipped with gas sensors for environmental monitoring and surveillance operations [4,5], [6][7][8][9][10][11] and also for radiation monitoring after a nuclear disaster [12][13][14]. Hence, this study aimed at evaluating a drone sensor platform to increase first responders' safety during early survey missions and improve monitoring activities in critical contexts.…”
Section: Introductionmentioning
confidence: 99%